Dynamic mechanical analysis and morphology of petroleum-based and bio-epoxy foams with wood filler - Alzomor, A.; M. Rus, A. Z.; A. Wahab, H.; M. Salim, N. S.; Marsi, N.; Zulhakimie, M. A.; M. Farid, M. (2021)
Current challenges highlight the need for polymer research using renewable natural sources as a substitute for petroleum-based polymers. In this study, consequently, the fabrication of green polyurethane (PU) foams and its composites is to be demonstrated dependent on synthesis in the laboratory scale of hydroxylated bio-epoxy (B) and petroleum-based synthetic-epoxy (E), crosslinker and wood fillers. Polyurethane foams were modified with two type of wood fiber fillers, powder (P) and flakes (L) with specific percentage ratios of 0, 5, 10, 15 and 20 %wt. Bio-epoxy (B) and synthetic-epoxy (E) foam and its composite were exposed to UV irradiation for a period of 2000 hours and 4000 hours by UV Whetherometer apparatus. The morphology structure and viscoelastic properties such as storage modulus, E', damping behavior, tan